A Journey through Invisibility in Ralph Ellison’s Invisible Man (LITERA KULTURA : Journal of Literary and Cultural Studies, 2017)
Abstract One of the most brilliant novel of all time that brings up racial issue is Invisible Man that was written by Ralph Ellison. It tells a journey of a nameless African-American man from South moving to urban life of Harlem. Through a sense of invisibility that seems to cloak him, he struggle with deception and racism in White dominant society. This study discusses about the invisibility process portrayed in the novel by using Franklin’s concept of invisibility. Moreover, the purpose of this study is to reveal and understand how invisibility is depicted in Invisible Man. This study is a literary research of African-American criticism that is conducted through descriptive qualitative and library research method by using Invisibility Syndrome Paradigm concept. The result of this study shows that through cumulative encounters with prejudice and racism experienced in his journey in Harlem, the protagonist struggles with invisibility for the lack of recognition, lack of satisfaction, lack of validation, lack of respect, lack of dignity toward his presence as equal human beings and eventually it leads to his identity being challenged and lost. After experienced series of unfortunate encounters of racial slights and people’s refusal to acknowledge and consider him as equal, he is rendered invisible in the eyes of the society. Keywords: invisibility, invisibility syndrome paradigm, racial slights, African-American criticism. Abstrak Salah satu dari novel paling brilian sepanjang masa yang mengangkat tentang isu rasial adalah novel Invisible Man yang ditulis oleh Ralph Ellison. Novel ini menceritakan tentang sebuah perjalanan dari seorang pria Afrika-America dari Selatan yang berpindah ke kehidupan kota Harlem. Dengan invisibilitas yang seakan menyelimutinya, dia berjuang melawan tipu-daya and rasisme dalam lingkungan sosial yang mana kaum putih lebih dominan. Penelitian ini membahas tentang proses invisibilitas yang tergambar dalam novel dengan menggunakan konsep invisibilitas milik Franklin. Selanjutnta, tujuan dari penelitian ini adalah untuk menyingkap dan memahami bagaimana invisibilitas digambarkan dalam Invisible Man. Penelitian ini merupakan penelitian kesastraan dari kritik sastra Afrika-Amerika yang dilakukan melalui metode penelitian deskripsi qualitatif dan kepustakaan dengan menggunakan konsep Paradigma Sindrom Invisibilitas . Hasil dari penelitian ini menunjukkan bahwa melalui pertemuan kumulatif dengan prasangka dan rasisme yang dialami dalam perjalanannya di Harlem, sang protagonis berjuang melalui invisibilitas ditandai dengan kurangnya pengakuan, penghargaan, validasi, rasa hormat, dan kurangnya martabat terhadap keberadaannya sebagai manusia yang sederajat dan berakibat pada identitasnya yang tergoyah dan hilang. Setelah mengalami banyak kejadian diskriminasi rasial dan juga penolakan masyarakat untuk mengakui dan menganggap dirinya mempunyai derajat yang sama, dia menjadi tidak terlihat di mata masyarakat. Kata Kunci: invisibilitas, paradigma sindrom invisibilitas, diskriminasi rasial, kritik sastra Afrika-Amerika.